Hybridization, polyploidization, and morphological convergence make dozens of taxa into one chaotic genetic pool: a phylogenomic case of the Ficus erecta species complex (Moraceae) - Wang, Xiaomei; Liao, Shuai; Zhang, Zhen; Zhang, Jianhang; Mei, Li; Li, Hongqing (Frontiers in Plant Science, 2024)
The Ficus erecta complex, characterized by its morphological diversity and frequent interspecific overlap, shares pollinating fig wasps among several species. This attribute, coupled with its intricate phylogenetic relationships, establishes it as an exemplary model for studying speciation and evolutionary patterns. Extensive researches involving RADseq (Restriction-site associated DNA sequencing), complete chloroplast genome data, and flow cytometry methods were conducted, focusing on phylogenomic analysis, genetic structure, and ploidy detection within the complex. Significantly, the findings exposed a pronounced nuclear-cytoplasmic conflict and discordance between gene trees and species trees. This evidence, together with genetic structure analysis, confirmed that hybridization within the complex is a frequent occurrence. The ploidy detection revealed widespread polyploidy, with certain species exhibiting multiple ploidy levels, including 2×, 3×, and 4×. Of particular note, only five species (F. abelii, F. erecta, F. formosana, F. tannoensis and F. vaccinioides) in the complex were proved to be monophyletic. Species such as F. gasparriniana, F. pandurata, and F. stenophylla were found to encompass multiple phylogenetically distinct lineages. This discovery, along with morphological comparisons, suggests a significant underestimation of species diversity within the complex. This study also identified F. tannoensis as an allopolyploid species originating from F. vaccinioide and F. erecta. Considering the integration of morphological, molecular systematics, and cytological evidences, it is proposed that the scope of the F. erecta complex be expanded to the entire subsect. Frutescentiae. This would redefine the complex as a continuously evolving group comprising at least 33 taxa, characterized by blurred species boundaries, frequent hybridization and polyploidization, and ambiguous genetic differentiation.